Association of low FVC spirometric pattern with WTC occupational exposures. (August 2020) - de la Hoz, Rafael E.; Shapiro, Moshe; Nolan, Anna; Celedón, Juan C.; Szeinuk, Jaime; Lucchini, Roberto G.
Abstract: Background: A reduced forced vital capacity without obstruction (low FVC) is the predominant spirometric abnormality reported in workers and volunteers exposed to dust, gases, and fumes at the World Trade Center (WTC) disaster site in 2001–2002. While low FVC has been associated with obesity and metabolic syndrome, its association with WTC occupational exposures has not been demonstrated. We estimated the prevalence of this abnormality and examined its association with WTC exposure level. Methods: Longitudinal study of the relation between arrival at the WTC site within 48 h and FVC below the lower limit of normal (FVC < LLN, with normal FEV1 /FVC ratio) at any time in 10, 284 workers with at least two spirometries between 2002 and 2018. Logistic regression and linear mixed models were used for the multivariable analyses. Results: The prevalence of low FVC increased from 17.0% (95% CI 15.4%, 18.5%) in June 2003, to 26.4% (95% CI 24.8%, 28.1%) in June 2018, and exceeded at both times that of obstruction. The rate of FVC decline was −43.7 ml/year during the study period. In a multivariable analysis adjusting for obesity, metabolic syndrome indicators, and other factors, early arrival at the WTC disaster site was significantly associated with low FVC, but only among men (ORadj  = 1.29, 95% CI 1.17, 1.43). Longitudinal FVC rate of decline did not differ by WTC site arrival time. Conclusions: Among WTC workers, the prevalence of low FVC increased over a 16-year period. Early arrival to the WTC disaster site was significantly associated with low FVC in males. Highlights: A reduced FVC without obstruction (low FVC) is a highly prevalent chronic airway phenotype. Low FVC is the most common spirometric abnormality in former WTC workers. Suboptimal effort, short exhalatory time, and obesity can cause low FVC. Low FVC was independently associated with early arrival at the WTC disaster site among men in this cohort.